Nas sendas do amor. uma reflexão sobre a Exortação Amoris Laetitia em diálogo com a modernidade líquida - Silva, Marivaldo Emidio da (2019)
This research intends to underpin an explanation about the conjugal love concept which we proposed to show how it develops in our contemporary society. The theoretical axis is mainly based in the bibliography from the sociologist named Zigmunt Bauman, especially discussing the literary work Amor Líquido, which shows a thinking about liquidity and fragments the human relationships through social studies of love. This theoretical basis will guide us in the discussion and will be related to the proposal from Papa Francisco in his “Exortação Apostólica - Amoris Laetitia”, as an identity presentation from a new Papacy or a new era: “Francisco’s era”. In this Exhortation, we will check that the Sovereign Pontiff conducts a dialogue with the new era inside the new cultural needs. Our aim is to show how the “baumoniana” liquidity also got inside the religious culture doing as its mainly essence, the two mainly commandments: to love God and the person who is beside you, which weakens constantly in this liquidity era. This research, which is bibliographically enforced, disposes of the next steps: selection and reflective reading from the bibliographic material, collecting different aspects that there are in the literary works proposed; delimitation and definition of the concept “love”, according to each author’s thoughts; selection and reflective reading from the publications in the social policy area and their affirmative laws; and reading from official religious speeches, according to the theme